An updated review on the diagnosis and assessment of post-treatment relapse in brain metastases using PET. (2nd November 2022) - Galldiks, Norbert; Wollring, Michael; Werner, Jan-Michael; Friedrich, Michel; Fink, Gereon R.; Langen, Karl-Josef; Lohmann, Philipp
ABSTRACT: Introduction: Brain metastases in patients with extracranial cancer are typically associated with increased morbidity and mortality. Stereotactic radiotherapy and immunotherapy using checkpoint inhibitors currently are essential in brain metastases treatment. Since conventional contrast-enhanced MRI alone cannot reliably differentiate between treatment-induced changes and brain metastasis relapse, several studies investigated the role of PET imaging and, more recently, radiomics, based on routinely acquired PET images, to overcome this clinically relevant challenge. Areas covered: The current literature on PET imaging, including radiomics, in patients with brain metastases, focusing on the diagnosis and assessment of post-treatment relapse, is summarized. Expert opinion: Available data suggest that imaging parameters, including radiomics features, mainly derived from amino acid PET, are helpful for diagnosis and assessment of post-treatment relapse in patients with brain metastases.